Analysis of Student Career Maturity Using Holland's Theory - Suci Mutia Lukman; Afdal Afdal; A Muri Yusuf (SCHOULID: Indonesian Journal of School Counseling, 2021)
The problem in this research is the high rate of student unemployment after graduating from school. One of the factors causing the high unemployment rate is students who do not know their own personality and work that suits their personality. This type of research is qualitative with a literature review approach, namely by using a way of, reading, searching, learning, and analyzing the contents of the book and is supported by several literatures that are related to the problem being studied. From the results of the analysis that has been done, it can be concluded that Holland's theory contributes to determining the career maturity of students.